Risk Factors Related to Mortality in COVID-19 Patients Hospitalized at Dr. Mohammad Hoesin General Hospital Palembang - Erianita, Nieke; Sari MP; Alfiah L (RSUP Dr Moh Hoesin Palembang, 2022)
The high risk of death for patients infected with COVID-19 has resulted in many stakeholders making policies and regulations related to COVID-19 in an effort to prevent the spread of this virus in Indonesia, starting from activating lockdowns, physical distancing to vaccinations in order to reduce morbidity and mortality rates. This study aimed to analyze various factors that could increase the risk of death of COVID-19 inpatients at Dr. Mohammad Hoesin General Hospital Palembang. The study uses the design of case-control by analyzing univariate, bivariate, and multivariates. The place of this research was carried out in Dr. Mohammad Hoesin General Hospital Palembang in the range of April until June 2020. It uses subjects based on study criteria. The result of bivariate analysis of the cause of death with independent variables based on data of COVID-19 claims in 2020. Statistically, there were some relationships among the gender (p-value=0,010), age (p-value=<0,0001), comorbid diseases (p-value=<0,0001), history of close contact with COVID-19 sufferers (p-value=0,006), length of stay (p-value=<0,0001). COVID-19 patients who have aged ≥50 years are at risk 2,74 to a higher risk of causing death than those aged <50 years after controlling for comorbid disease variables and length of stay (95% CI: 1,84-4.07). In conclusion, age is the dominant factor causing death. It can be used as a policy reference and additional information for readers. To apply the health protocols correctly and always consume nutritious food, especially for risky groups.